HUBUNGAN AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF LANSIA - Etika Dewi Cahyaningrum (Jurnal Surya Muda, 2022)
Young elderly dominate the prevalence of the elderly in Indonesia with the age of 60-69 at 63.39%, then the middle elderly with the age of 70-79 years by 27.92% and the elderly aged 80 years and over by 8.69%. Functional changes in the elderly are decreased cognitive function, resulting in changes in the structure of brain function. This will be seen in the elderly who have impaired orientation, attention, concentration, thinking, remembering, and language. The purpose of this study was to determine the relationship between physical activity and cognitive function of the elderly. This research uses correlational analytic method and cross sectional approach. The instrument used was a questionnaire and the cognitive function of the elderly was measured by the Mini Mental State Examination (MMSE). The sampling technique used purposive sampling with 92 elderly respondents. Statistical analysis used is frequency distribution and chi-square. This research shows that elderly with light physical activity mostly have cognitive impairment, that is 39 people (42.4%). The results of the analysis showed that the p-value was 0.00 < 0.05 so that there was a relationship between physical activity and cognitive function of the elderly. Physical activity reduces the incidence of various vascular disease factors such as hypertension, obesity, and diabetes. Cardiovascular function can be improved with intense physical activity. As blood flow increases, oxygen transport to the brain increases. Cognitive function of the elderly can be maintained with regular physical activity so that it remains at a good level.